Localized hypermutation and associated gene losses in legume chloroplast genomes - Magee, Alan M.; Aspinall, Sue; Rice, Danny W.; Cusack, Brian P.; Sémon, Marie; Perry, Antoinette S.; Stefanović, Saša; Milbourne, Dan; Barth, Susanne; Palmer, Jeffrey D.; Gray, John C.; Kavanagh, Tony A.; et al. (Genome Research, 2010)
Point mutations result from errors made during DNA replication or repair, so they are usually expected to be homogeneous across all regions of a genome. However, we have found a region of chloroplast DNA in plants related to sweetpea (Lathyrus) whose local point mutation rate is at least 20 times higher than elsewhere in the same molecule. There are very few precedents for such heterogeneity in any genome, and we suspect that the hypermutable region may be subject to an unusual process such as repeated DNA breakage and repair. The region is 1.5 kb long and coincides with a gene, ycf4, whose rate of evolution has increased dramatically. The product of ycf4, a photosystem I assembly protein, is more divergent within the single genus Lathyrus than between cyanobacteria and other angiosperms. Moreover, ycf4 has been lost from the chloroplast genome in Lathyrus odoratus and separately in three other groups of legumes. Each of the four consecutive genes ycf4-psaI-accD-rps16 has been lost in at least one member of the legume “inverted repeat loss” clade, despite the rarity of chloroplast gene losses in angiosperms. We established that accD has relocated to the nucleus in Trifolium species, but were unable to find nuclear copies of ycf4 or psaI in Lathyrus. Our results suggest that, as well as accelerating sequence evolution, localized hypermutation has contributed to the phenomenon of gene loss or relocation to the nucleus.